Medición de la calidad de vida de los niños del sector marginado del pantano cantón Quevedo periodo 2012-2014 - León Coello, Gladys Yolanda (2015)
The El Pantano, is settled on the banks of rivers Quevedo, its population is approximately 300 inhabitants consisting of 75 households. The people living in the area of El Pantano are devoted to agriculture-related economic activities, building trade, crafts, among others, that support families and are the main ingredient that provides the financial resources for growth and development of the quality of life of the population groups in the community. The method adopted to measure quality of life, has to do with the rate of dimensional poverty and Gencat scale application, finding that girls and girls Swamp industry have a quality of life with a grade average of between 50 % and 80%. The 62.72% of household heads surveyed consider that the children do not have what it takes to have a good quality of life, according to the 8462%, these if they do their best for their children to welfare. The 75.74% of the surveyed population does not consider that sufficient availability of money encourages an adequate quality of life. 36.69% according to the affection and love that professes to children are essential to reaching a level appropriate level, to which health and education are added. To this end, the Government of Econ. Rafael Correa has contributed favorably, as expressed by 80.47%. You also need to make a proposal for economic and social development in the amount of USD 331 319, distributed in a social development plan with an investment of USD 94694 to USD 331 319 and economic.